2002
DOI: 10.1200/jco.2002.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Intravenous Ibandronate Therapy on Skeletal-Related Events, Survival, and Bone Resorption Markers in Patients With Advanced Multiple Myeloma

Abstract: Monthly injections of ibandronate 2 mg IV neither reduced bone morbidity nor prolonged survival in the overall population of stage II/III multiple myeloma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(80 citation statements)
references
References 28 publications
3
73
0
4
Order By: Relevance
“…Serum markers are especially convenient as blood is often being taken for other purposes (though diurnal variation is a problem for serum) and serum measurement avoids complex urine collection and creatinine correction. A recent study of ibandronate in multiple myeloma (Menssen et al, 2002) demonstrated that patients experienced significantly fewer skeletal-related events per patient year when the ibandronate dose selected effectively suppressed the bone turnover markers serum osteocalcin and urinary Ctx. This study also found that patients experiencing a defined reduction in both bone markers suffered fewer events than in those with reduction in only one marker, raising the possibility that an index comprising more than one bone marker may add further predictive value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum markers are especially convenient as blood is often being taken for other purposes (though diurnal variation is a problem for serum) and serum measurement avoids complex urine collection and creatinine correction. A recent study of ibandronate in multiple myeloma (Menssen et al, 2002) demonstrated that patients experienced significantly fewer skeletal-related events per patient year when the ibandronate dose selected effectively suppressed the bone turnover markers serum osteocalcin and urinary Ctx. This study also found that patients experiencing a defined reduction in both bone markers suffered fewer events than in those with reduction in only one marker, raising the possibility that an index comprising more than one bone marker may add further predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…However, with few exceptions (Lipton et al, 1998;Menssen et al, 2002), little work has been carried out on the possible correlation between bone markers and the occurrence of skeletal events in metastatic bone disease. If such a link can be firmly established, then it may be appropriate to direct the management of patients with metastatic bone disease to maintain or lower an individual's bone marker values into the normal range.…”
mentioning
confidence: 99%
“…71 Bone markers during anti-resorptive therapy Biochemical markers of bone turnover have been used in MM both to monitor bisphosphonate treatment, and to determine 71 Terpos et al showed that the addition of pamidronate to CC significantly reduced urinary NTX and disease-related pain compared with CC alone, 49 and that pamidronate in combination with interferon-a induced bone formation in MM patients at plateau phase. 61 Ibandronate at a dose of 2 mg showed a substantial reduction of CTX and OC in only one-third of MM patients, 74 whereas in a randomized study, monthly pamidronate (90 mg, IV) produced a greater reduction of NTX and TRACP-5b compared with monthly ibandronate (4 mg, IV). 56,75 In a large, randomized study comparing 4 mg zoledronic acid with 90 mg pamidronate, given IV every 3-4 weeks in patients with bone metastases from breast cancer or with MM osteolytic disease, urinary NTX was strongly suppressed (up to 64% below baseline in both treatment groups) for the duration of the study.…”
Section: Correlations Of Bone Turnover Markers With Myeloma Activity mentioning
confidence: 99%
“…ibandronate does not appear to compromise renal safety, including in patients with urologic cancer and compensated renal insufficiency [51]. Few studies have investigated the efficacy of ibandronate in patients with MM [52,53]. However, available data suggest that ibandronate is well tolerated in this indication, even in elderly patients with pre-existing renal failure [53,54].…”
Section: Ibandronatementioning
confidence: 99%